Impact of the SARS‐CoV‐2 pandemic on the health of individuals with intoxication‐type metabolic diseases—Data from the E‐IMD consortium. Issue 2 (14th November 2022) - Mütze, Ulrike; Gleich, Florian; Barić, Ivo; Baumgartner, Mathias; Burlina, Alberto; Chapman, Kimberly A.; Chien, Yin‐Hsiu; Cortès‐Saladelafont, Elisenda; De Laet, Corinne; Dobbelaere, Dries; Eysken, Francois; Gautschi, Matthias; et al.
Abstract: The SARS‐CoV‐2 pandemic challenges healthcare systems worldwide. Within inherited metabolic disorders (IMDs) the vulnerable subgroup of intoxication‐type IMDs such as organic acidurias (OA) and urea cycle disorders (UCD) show risk for infection‐induced morbidity and mortality. This study (observation period February 2020 to December 2021) evaluates impact on medical health care as well as disease course and outcome of SARS‐CoV‐2 infections in patients with intoxication‐type IMDs managed by participants of the European Registry and Network for intoxication type metabolic diseases Consortium (E‐IMD). Survey's respondents managing 792 patients ( n = 479 pediatric; n = 313 adult) with intoxication‐type IMDs ( n = 454 OA; n = 338 UCD) in 14 countries reported on 59 (OA: n = 36; UCD: n = 23), SARS‐CoV‐2 infections (7.4%). Medical services were increasingly requested (95%), mostly alleviated by remote technologies (86%). Problems with medical supply were scarce (5%). Regular follow‐up visits were reduced in 41% (range 10%–50%). Most infected individuals (49/59; 83%) showed mild clinical symptoms, while 10 patients (17%; n = 6 OA including four transplanted MMA patients; n = 4 UCD) were hospitalized (metabolic decompensation in 30%). ICU treatment was not reported. Hospitalization rate did not differ for diagnosis or age group ( p = 0.778). Survival rate was 100%. Full recovery was reported for 100% in outpatient care and 90% of hospitalized individuals. SARS‐CoV‐2 impacts health care of individuals with intoxication‐type IMDs worldwide. Most infected individuals, however, showed mild symptoms and did not require hospitalization. SARS‐CoV‐2‐induced metabolic decompensations were usually mild without increased risk for ICU treatment. Overall prognosis of infected individuals is very promising and IMD‐specific or COVID‐19‐related complications have not been observed.